2022
DOI: 10.3390/v14020336
|View full text |Cite
|
Sign up to set email alerts
|

Risk of Vaccine Breakthrough SARS-CoV-2 Infection and Associated Factors in Healthcare Workers of Trieste Teaching Hospitals (North-Eastern Italy)

Abstract: Background: Healthcare workers (HCWs) are particularly exposed to biological risk, including SARS-CoV-2 infection. In order to contrast the current pandemic and alleviate the burden of the disease on the healthcare system, a mass vaccination campaign against COVID-19 has been launched worldwide. Aim To evaluate the impact of COVID-19 vaccination in HCWs exposed to SARS-CoV-2, to describe the clinical presentation of COVID-19 in infected HCWs, and to investigate clinical and occupational risk factors for breakt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
29
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 41 publications
7
29
3
Order By: Relevance
“…Furthermore, occupation was not a significant risk factor in the present study, which is in line with some studies investigating the risk of both NPSs positivity [32] and seropositivity [18,23,38,39]. Some authors identified a decreased risk for doctors and nurses and an increased risk for technicians and sanitation workers [16,28,40] although another study from Trieste teaching hospitals found a higher risk of SARS-CoV-2 infection in nurse aides/auxiliary personnel and a lower risk for technicians [41]. The lack of significance could be related to our inclusion criteria, which only allowed recruitment of HCWs exposed to COVID-19 patients, thus exposed to high risk of infection regardless of job task.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 89%
“…Furthermore, occupation was not a significant risk factor in the present study, which is in line with some studies investigating the risk of both NPSs positivity [32] and seropositivity [18,23,38,39]. Some authors identified a decreased risk for doctors and nurses and an increased risk for technicians and sanitation workers [16,28,40] although another study from Trieste teaching hospitals found a higher risk of SARS-CoV-2 infection in nurse aides/auxiliary personnel and a lower risk for technicians [41]. The lack of significance could be related to our inclusion criteria, which only allowed recruitment of HCWs exposed to COVID-19 patients, thus exposed to high risk of infection regardless of job task.…”
Section: Interpretation Of Findings In Relation To Other Studiessupporting
confidence: 89%
“…We believe that reduced lethality in Serrana was probably due to the anticipated vaccination program, where, by this time, 80.1% of the adult population was vaccinated. The beneficial effects of the vaccination were also observed in other studies where fully vaccinated individuals were less likely to acquire symptomatic or asymptomatic infections [ 27 ]. Therefore, the COVID-19 vaccination shows beneficial effects in reducing the SARS-CoV-2-related infection rates, severe cases, and mortality.…”
Section: Discussionsupporting
confidence: 66%
“…Given the concerns about vaccine breakthrough infections [ 20 ], studies have been conducted to confirm vaccine breakthrough infections with SARS-CoV-2 variants using genome sequencing [ 16 ] and to investigate clinical characteristics of the vaccine breakthrough infections [ 21 - 23 ]. Early reports have found breakthrough infections more often occur in individuals with solid organ transplants [ 24 - 27 ], obesity [ 28 ], hypertension [ 29 ], diabetes [ 29 , 30 ], congestive heart failure [ 29 , 31 ], chronic kidney disease (CKD) [ 22 , 32 ], lung diseases [ 33 ], dementia [ 34 ], and cancer [ 22 , 35 - 37 ]. Here, we retrospectively analyzed electronic health records (EHRs) from the Columbia University Irving Medical Center/New York Presbyterian (CUIMC/NYP) up to September 21, 2021, to systematically identify risk factors associated with breakthrough infections among fully messenger RNA (mRNA)–vaccinated individuals.…”
Section: Introductionmentioning
confidence: 99%